2006
DOI: 10.1590/s0103-64402006000400005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface treatment on the shear bond strength of a resin-based cement to porcelain

Abstract: The purpose of this in vitro study was to evaluate the effect of different surface treatments on the shear bond strength of a resin-based cement to porcelain. Sixty pairs of 50% aluminous porcelain discs were fabricated. In each pair, one disc measured 6 mm in diameter X 3 mm thickness (A) and the other measured 3 mm in diameter X 3mm thickness (B). The specimens were randomly assigned to 6 groups (n=10 pairs of discs), according to the surface treatment: etching with 10% hydrofluoric acid for 2 or 4min (G1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 13 publications
3
35
0
2
Order By: Relevance
“…Although clinicians should follow the manufacturers' recommendations for bonding procedures, a 60 s etching time for bonding to feldspathic ceramic might be recommended. However, care should be taken when selecting the etching time for each substrate, as previous studies have shown negative effects of over-etching ceramics, such as difficult penetration of the bonding agent into the irregularities and possible cohesive failure of the substrate (1)(2)(3)(4)19,20). On the other hand, although the light source presented …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although clinicians should follow the manufacturers' recommendations for bonding procedures, a 60 s etching time for bonding to feldspathic ceramic might be recommended. However, care should be taken when selecting the etching time for each substrate, as previous studies have shown negative effects of over-etching ceramics, such as difficult penetration of the bonding agent into the irregularities and possible cohesive failure of the substrate (1)(2)(3)(4)19,20). On the other hand, although the light source presented …”
Section: Discussionmentioning
confidence: 99%
“…The literature presents, however, controversial findings regarding the etching time required for optimal bonding to ceramic. While some authors (1)(2)(3) found lower bond strengths associated with increasing etching times, others (4,5) observed that longer etching times may increase the bond strength to ceramic.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this disadvantage, HF acid etching is routinely used for orthodontic bonding prior to bonding brackets to various ceramics [4,11,12]. The bond strength of resin composite to feldspathic ceramic is higher with HF etching followed by silanization than without [13,14]. An alternative to HF is tribochemical silica coating that is based on labside (Rocatec system, 110 µm, 3M ESPE, St. Paul, MN, USA; ) or charside (CoJet, 30 µm, 3M ESPE) particle deposition methods using silica-coated alumina particles followed by silane application [1,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This confirms the effectiveness of the siloxane bond between the silica compounds in the glass phase of the ceramic and the methacrylate groups in the cement. 3,5,6,14,20 Nevertheless, the only subgroup that did not have a normal data distribution was the PC subgroup. It is possible that use of the silane agent alone is not sufficient to achieve reliable values of bond strength between the ceramic surface and resin cement, a hypothesis that is supported by the findings of a study by Matinlinna and others.…”
Section: Discussionmentioning
confidence: 99%
“…9 The surfaces of pressable glass-ceramic restorations are rough and thus provide a degree of inherent mechanical retention. The standardization of the surfaces of ceramic materials with silicon carbide paper (SiC) and diamond pastes in many previous studies 4,[10][11][12][13][14][15][16][17][18] was intended to remove any preexisting mechanical retention that could interfere with bond-strength tests. This treatment produced a flat, polished ceramic surface that enabled the conditioning effect of hydrofluoric acid and the abrasive effect of sandblasting with 50-lm aluminum oxide on the bond strength between the resin cement and glass ceramic to be determined separately.…”
Section: Introductionmentioning
confidence: 99%